2022
DOI: 10.1155/2022/2249749
|View full text |Cite
|
Sign up to set email alerts
|

Role of Molecular Hydrogen in Ageing and Ageing-Related Diseases

Abstract: Ageing is a physiological process of progressive decline in the organism function over time. It affects every organ in the body and is a significant risk for chronic diseases. Molecular hydrogen has therapeutic and preventive effects on various organs. It has antioxidative properties as it directly neutralizes hydroxyl radicals and reduces peroxynitrite level. It also activates Nrf2 and HO-1, which regulate many antioxidant enzymes and proteasomes. Through its antioxidative effect, hydrogen maintains genomic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 196 publications
0
15
0
Order By: Relevance
“…However, in 2007, scholars discovered that H 2 can exert antioxidant properties and prevent ischemia-reperfusion injury in a rat model (Ohsawa et al, 2007). Since then, a large number of studies have explored the therapeutic and preventive effects of H 2 in different diseases, including metabolic diseases, neurological diseases, cancer, and many aging-related diseases (Liu et al, 2020;Liu et al, 2021;Fu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…However, in 2007, scholars discovered that H 2 can exert antioxidant properties and prevent ischemia-reperfusion injury in a rat model (Ohsawa et al, 2007). Since then, a large number of studies have explored the therapeutic and preventive effects of H 2 in different diseases, including metabolic diseases, neurological diseases, cancer, and many aging-related diseases (Liu et al, 2020;Liu et al, 2021;Fu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative damage to proteins is divided in two categories, including the reversible and irreversible protein modifications ( Caliri et al, 2021 ; Fu et al, 2022 ). Protein carbonylation is an irreversible protein modification, resulting from oxidative damage, that often leads to loss of protein function ( Matsuo et al, 2021 ).…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Clinical studies on hydrogen have demonstrated its potential application for cognitive impairment [ 9 ], metabolic syndrome [ 10 ], stroke [ 11 ], COVID-19 [ 12 ], and in exercise medicine [ 7 ]. The clinical and molecular effects of hydrogen gas have been extensively reviewed [ 13 , 14 ].…”
Section: Physicochemical Properties and Biological Effects Of Molecul...mentioning
confidence: 99%